2021
DOI: 10.4103/jiaps.jiaps_235_20
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Carcinoma Thyroglossal Cyst

Abstract: Thyroglossal cyst is the most common congenital neck anomaly in children with equal sex incidence, but papillary carcinoma of the thyroglossal cyst in children is rare with only 10 cases reported so far. Even in adults, the incidence of malignancy in the thyroglossal cyst is only 1%. Most cases are diagnosed following surgery on histopathological examination; there is no consensus on the management owing to this rarity and indolent but unpredictable behavior of thyroid cancers. Here, we present one such rare c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the pT3 cases, Sistrunk procedure was performed, and total thyroidectomy was advocated. In Pandey et al, 2021, the patient did not undergo total thyroidectomy as parents refused a second operation. Shankar et al, 2015 were convinced about the patient needing a subsequent total thyroidectomy, radioactive iodine ablation and thyroxine suppression.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pT3 cases, Sistrunk procedure was performed, and total thyroidectomy was advocated. In Pandey et al, 2021, the patient did not undergo total thyroidectomy as parents refused a second operation. Shankar et al, 2015 were convinced about the patient needing a subsequent total thyroidectomy, radioactive iodine ablation and thyroxine suppression.…”
Section: Case Reportmentioning
confidence: 99%
“…In terms of follow up, most authors remain vague with regards to follow up duration and methods. For instance, Pandey et al, 2021 reported that lymphovascular invasion was noted post operatively after a Sistrunk procedure and that parents declined total thyroidectomy and bilateral lymph node dissection. However, the authors wrote that after 2 years of follow up, the patient's repeat US of neck did not show any abnormality in the thyroid or lymphadenopathy.…”
Section: Case Reportmentioning
confidence: 99%